1999
DOI: 10.1002/chin.199927026
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Thermal Stability and Phase Transformations in CuBi2O4.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…The lattice parameters of the CuBi 2 O 4 film were calculated using the highest intensity peaks in the XRD diffractogram at 20.91 and 28.07°, corresponding to the (200) and (211) indices, respectively. The parameters are found to be a = b = 8.499 Å and c = 5.803 Å, which is in close agreement with other reports in the literature. Using these parameters the bulk density of the CuBi 2 O 4 films is 8.645 g/cm 3 . The CuBi 2 O 4 crystal structure is shown in Figure .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The lattice parameters of the CuBi 2 O 4 film were calculated using the highest intensity peaks in the XRD diffractogram at 20.91 and 28.07°, corresponding to the (200) and (211) indices, respectively. The parameters are found to be a = b = 8.499 Å and c = 5.803 Å, which is in close agreement with other reports in the literature. Using these parameters the bulk density of the CuBi 2 O 4 films is 8.645 g/cm 3 . The CuBi 2 O 4 crystal structure is shown in Figure .…”
Section: Resultssupporting
confidence: 86%
“…The mineral name for CuBi 2 O 4 is kusachiite. It has been reported to have a tetragonal crystal structure with space group P 4/ ncc , a = b = 8.500–8.511 Å, c = 5.814–5.823 Å, Z = 4. To determine the crystal structure of our CuBi 2 O 4 photocathodes we measured them by X-ray diffraction (XRD). Figure shows the XRD diffractogram for a CuBi 2 O 4 photocathode synthesized by drop-casting on a fluorine-doped tin oxide (FTO) coated glass substrate followed by annealing at 450 °C.…”
Section: Resultsmentioning
confidence: 99%
“…This is attributed to the current-doubling effect of the H 2 O 2 electron scavenger. [23] It was also found that the acceptor density (N A ) of ≈3 × 10 18 cm −3 calculated from Equation (1) using the slope of the Mott-Schottky plots and the reported dielectric constant (ε = 80) of CBO, [49] their flat band potential, and acceptor density were similar to that of previous report on CBO polycrystalline thin films. [23] It suggests that the crystallinity difference between the CBO polycrystalline thin film and the CBO single-crystal thin film photocathode rarely influence the intrinsic p-type semiconducting properties of CBO…”
Section: Resultssupporting
confidence: 83%
“…The films were crystallized by annealing at 823 K. The X-ray diffraction (XRD) peak intensity of the film prepared at 873 K was lower than those of the 773 and 823 K cases (Figure c). High temperature can induce evaporation of Bi and decomposition of CuBi 2 O 4 , reducing the amount of the CuBi 2 O 4 phase formed on FTO . The XRD peak intensities increased with an increasing number of layers (Figure d).…”
supporting
confidence: 65%
“…High temperature can induce evaporation of Bi and decomposition of CuBi 2 O 4 , reducing the amount of the CuBi 2 O 4 phase formed on FTO. 25 The XRD peak intensities increased with an increasing number of layers (Figure 1d). The absorbance of CuBi 2 O 4 films was measured using UV−vis spectroscopy (Figure 1a, Figure S2).…”
mentioning
confidence: 96%